COGNITIVE BIAS EFFECTS ON POLYTECHNIC STUDENTS’ INVESTMENT DECISIONS IN SEMARANG - Dwi Andriani; Dina Yeni Martia; Dzulqarnaen Arief Mustofa; Mutiara Febrianti; Rini Setiyani; Xarista Christy (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
The rapid growth of young investors in Financial reflects increasing engagement with the capital market, yet novice investors remain vulnerable to cognitive biases in decision-making. This study investigates the influence of self-attribution bias (internal and external), confirmation bias, and overconfidence bias on investment decision-making among undergraduate Polytechnic students in Semarang. A quantitative research design was employed using a structured questionnaire, and the data collected from 117 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that internal self-attribution bias significantly affects investment decisions, both directly and through its mediating role in overconfidence bias. In contrast, confirmation bias showed a financially significant effect on investment behavior. The study concludes that internal psychological attributions, particularly beliefs in personal competence, are key drivers of student investor behavior. These results underscore the importance of integrating behavioral finance and awareness of cognitive biases into financial education to support more rational, informed investment decisions.